ORIGIN OF FLUIDS IN IRON OXIDE–COPPER–GOLD DEPOSITS: CONSTRAINTS FROM δ 37CL, 87SR/86SRI AND CL/BR - Chiaradia M.; Banks D.; Cliff R.; Marschik R.; De haller A. (My University, 2006)
The origin of the hypersaline fluids (magmatic or basinal brine?), associated with iron oxide (Cu–U–Au–REE) deposits, is controversial. We report the first chlorine and strontium isotope data combined with Cl/Br ratios of fluid inclusions from selected iron oxide–copper–gold (IOCG) deposits (Candelaria, Raúl–Condestable, Sossego), a deposit considered to represent a magmatic end member of the IOCG class of deposit (Gameleira), and a magnetite–apatite deposit (El Romeral) from South America. Our data indicate mixing of a high δ 37Cl magmatic fluid with near 0‰ δ 37Cl basinal brines in the Candelaria, Raúl–Condestable, and Sossego IOCG deposits and leaching of a few weight percent of evaporites by magmatic-hydrothermal (?) fluids at Gameleira and El Romeral. The Sr isotopic composition of the inclusion fluids of Candelaria, Raúl–Condestable, and El Romeral confirms the presence of a non-magmatic fluid component in these deposits. The heavy chlorine isotope signatures of fluids from the IOCG deposits (Candelaria, Raúl–Condestable, Sossego), reflecting the magmatic-hydrothermal component of these fluids, contrast with the near 0‰ δ 37Cl values of porphyry copper fluids known from the literature. The heavy chlorine isotope compositions of fluids of the investigated IOCG deposits may indicate a prevailing mantle Cl component in contrast to porphyry copper fluids, an argument also supported by Os isotopes, or could result from differential Cl isotope fractionation processes (e.g. phase separation) in fluids of IOCG and porphyry Cu deposits.
Keywords: CHLORINE ISOTOPES; STRONTIUM ISOTOPES; IRON OXIDE-COPPER-GOLD DEPOSITS; CHILE; PERU; BRAZIL